Design of an open pod air intake system for the turbocarged Proton Gen-2 - Mah, Christopher Heen Meng, 1988-; Srithar Rajoo, supervisor; Fakulti Kejuruteraan Mekanikal (2012)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012